The zoospores of the thraustochytrid Aurantiochytrium limacinum: Transcriptional reprogramming and lipid metabolism associated to their specific functions. (16th March 2020) - Dellero, Younès; Maës, Cécile; Morabito, Christian; Schuler, Martin; Bournaud, Caroline; Aiese Cigliano, Riccardo; Maréchal, Eric; Amato, Alberto; Rébeillé, Fabrice
Summary: Aurantiochytrium limacinum (Thraustochytriaceae, class Labyrinthulomycetes) is a marine Stramenopile and a pioneering mangrove decomposer. Its life cycle involves a non‐motile stage and zoospore production. We observed that the composition of the medium, the presence of amino acids in particular, affects the release of zoospores. Two opposite conditions were defined, one with a cell population mainly composed of zoospores and another one with almost only non‐motile cells. In silico allelic frequency analysis and flow cytometry suggest that zoospores and non‐motile cells share the same ploidy level and are diploid. Through an RNA‐seq approach, the transcriptional reprogramming accompanying the formation of zoospores was investigated, with a particular focus on their lipid metabolism. Based on a differential expression analysis, zoospores are characterized by high motility, very active signal transduction, an arrest of the cell division, a low amino acid metabolism and low glycolysis. Focusing on lipid metabolism, genes involved in lipase activities and peroxisomal β‐oxidation are upregulated. qRT‐PCR of selected lipid genes and lipid analyses during the life span of zoospores confirmed these observations. These results highlight the importance of the lipid dynamics in zoospores and show the metabolic processes required to use these energy‐dense molecules as fuel for zoospore survival during their quest of new territories.